Landscape Design Approach in Heritage Context (Case study: Emmahaven Port Coal Storage Facilities Sawahlunto City, West Sumatra) - Baritoadi Buldan Rayaganda Rito; Noor Cholis Idham (Departement of Architecture, Universitas Islam Indonesia, 2019)
Sawahlunto City was a famous Coal Mining City in West Sumatera dates back from the Dutch colonial period. However, the sharp decline of its mining productivity in 2000 posed a threat to the sustainability of city life. To overcome this problem, the Government changed the direction of the development of once a dominant mining city to become a tourism city, as stated in the city’s vision on the Regional Regulation “Sawahlunto Becomes coal Mining heritage Tourism City by 2020 “. To get world recognition of its potential, the city of Sawahlunto is registered to UNESCO’s world heritage city tentative list in 2015 and continued the process for final heritage list. As part of that process, this research is dealing with how to transform the existing landscape area of the Emmahaven Port coal storage facilities as a part of an important heritage area in Sawahlunto, by applying the Outstanding Universal Value (O.U.V) of the area within its landscape design. The OUV in the form of tangible and intangible values are applied to create the place character of the industrial atmosphere by material selection, creating visual integrity and spatial character by using the Silo and the coal transportation catwalk supporting structures as points of interest, as well as providing facilities to promote cultural and social interaction.Keywords: world heritage list, UNESCO, outstanding universal value, Sawahlunto heritage city, sense of place, place character, landscape design form and space, infill design in heritage context